2021
DOI: 10.18632/aging.203204
|View full text |Cite
|
Sign up to set email alerts
|

Association between Alzheimer’s disease genes and trajectories of cognitive function decline in Han Chinese in Taiwan

Abstract: Genetic background has been considered one of the important contributors to the rate of cognitive decline among patients with Alzheimer’s disease (AD). We conducted a 4-year longitudinal follow-up study, recruited 255 AD and 44 mild cognitive impairment (MCI) patients, and used a data-driven trajectory analysis to examine the influence of selected AD risk genes on the age for and the rate of cognitive decline in Han Chinese population. Genotyping of selected single-nucleotide polymorphisms in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Normative data for many cortical and subcortical structures differed between ADNI and OASIS non‐Hispanic White participants and those in a second Korean cohort, affecting the performance of predictive algorithms 316 . Beyond the APOE ε4 allele, additional predictive associations were reported between alleles in ABCA7 and SORL1 and cognitive decline in a Han Chinese population from Taiwan compared to ADNI 317 …”
Section: Are Adni Results Generalizable?mentioning
confidence: 97%
See 2 more Smart Citations
“…Normative data for many cortical and subcortical structures differed between ADNI and OASIS non‐Hispanic White participants and those in a second Korean cohort, affecting the performance of predictive algorithms 316 . Beyond the APOE ε4 allele, additional predictive associations were reported between alleles in ABCA7 and SORL1 and cognitive decline in a Han Chinese population from Taiwan compared to ADNI 317 …”
Section: Are Adni Results Generalizable?mentioning
confidence: 97%
“… 316 Beyond the APOE ε4 allele, additional predictive associations were reported between alleles in ABCA7 and SORL1 and cognitive decline in a Han Chinese population from Taiwan compared to ADNI. 317 …”
Section: Are Adni Results Generalizable?mentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted single-nucleotide polymorphism (SNP) analyses and genome-wide association studies have validated the association not only in populations of Caucasian origin but also in Asian populations (Reitz et al, 2011;Lambert et al, 2013;Miyashita et al, 2013). A number of studies have shown significant associations between specific SORL1 polymorphisms and various phenotypes in AD patients, including lower Aβ levels in cerebrospinal fluid (Alexopoulos et al, 2011) and serum (Chou et al, 2016), increased tau protein in cerebrospinal fluid (Louwersheimer et al, 2015), hippocampal atrophy (Cuenco et al, 2008;Louwersheimer et al, 2015;Xiromerisiou et al, 2021), white matter hyperintensity (Cuenco et al, 2008), frontal symptoms (Huang et al, 2020), rate of cognitive decline (Hsieh et al, 2021), and Parkinsonian features (Cuccaro et al, 2016;Xiromerisiou et al, 2021).…”
Section: Introductionmentioning
confidence: 98%